2011
DOI: 10.1111/j.1440-172x.2011.01976.x
|View full text |Cite
|
Sign up to set email alerts
|

The complementary and alternative medicine use among asthma and chronic obstructive pulmonary disease patients in the southern region of Turkey

Abstract: The aim of this descriptive study was to investigate the complementary and alternative medicine (CAM) applications and factors associated and its use among asthma and chronic obstructive pulmonary disease (COPD) patients in the southern region of Turkey. The study sample consisted of 197 patients. A percentage of 86.3 of asthma and COPD patients used at least one type of CAM. The most commonly used CAM methods are deep inhalation (51.8%), herb or herbal tea (46.7%), praying (41.1%) and applying vapour (36%). P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 42 publications
2
24
0
4
Order By: Relevance
“…Healthcare professionals'knowledge of the factors which ease or blocks the use of CAM is important in order to protect the health of the elderly population and maintain their safety. In the literature, it has been stated that patients/elderly who used CAM do not inform healthcare personnel, also healthcare personnel do not question CAM usage 12,15,18,30 . Health professionals should assess for CAM use and increase their understanding about the kind and reason of the CAM therapies for comprehensive and qualified care.…”
Section: Araştirma Makalesi̇ / Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Healthcare professionals'knowledge of the factors which ease or blocks the use of CAM is important in order to protect the health of the elderly population and maintain their safety. In the literature, it has been stated that patients/elderly who used CAM do not inform healthcare personnel, also healthcare personnel do not question CAM usage 12,15,18,30 . Health professionals should assess for CAM use and increase their understanding about the kind and reason of the CAM therapies for comprehensive and qualified care.…”
Section: Araştirma Makalesi̇ / Research Articlementioning
confidence: 99%
“…CAM usage in Turkey had been subject of some studies. In these studies, the percentage of CAM usage varies between 35.3% and 86.3% [10][11][12][13][14][15] . In studies carried out on elderly individuals, the percentage of CAM usage varies between 27.7% and 88% 8,[16][17][18][19][20][21][22][23][24][25][26] .…”
Section: Araştirma Makalesi̇ / Research Articlementioning
confidence: 99%
“…On the one hand, the benefits arising from the use of particular CAM therapies are recognized for some diseases such as cancer, asthma, diabetes, cardiovascular diseases, liver diseases and rheumatology (9)(10)(11)(12). On the other hand, these benefits lack thorough scientific and clinical evidence (13)(14)(15).…”
Section: Implications For Policy Makersmentioning
confidence: 99%
“…Complementary and alternative medicine (CAM) is still popular worldwide [1][2][3][4][5][6] as it is reflected in the prevalence data of CAM use that varied between 9.8% and 76% among general population [1][2][3][4][5][6][7]. A systematic review of surveys from the UK also reported that 51.8% of the population applied alternative methods at least once during their lifetime [8].…”
Section: Introductionmentioning
confidence: 99%